Iterative Schemes of General Restricted Linear Equation: A novel approach in solving general restricted linear equations using iterative schemes (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Newton iterative strategy for processing external inverses with recommended range and invalid space is utilized in the non-stationary Richardson iterative technique to build up an iterative technique for illuminating general limited linear conditions. Beginning with any appropriately picked introductory repeat, our strategy creates an arrangement of emphasizes meeting to the arrangement. The important and adequate conditions for the intermingling alongside the blunder limits are built up. The utilizations of the iterative strategy for fathoming some extraordinary linear conditions are additionally examined. Various numerical precedents are worked out.